ANALISIS DAMPAK LALU LINTAS PUSAT PEMERINTAHAN “MANGUPRAJA MANDALA” KABUPATEN BADUNG TERHADAP KINERJA JALAN YANG ADA DI SEKITARNYA - Putu Alit Suthanaya; Dewa Made Priyantha Wedagama; Kadek Lendi Sabinawa (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2019)
TRAFFIC IMPACT ANALYSIS OF BADUNG REGENCY GOVERNMENT CENTRE “MANGUPRAJA MANDALA” ON THE PERFORMANCE OF SURROUNDING ROADSABSTRACTTraffic congestion around Hanoman intersection especially during the rush hours when the employees of the Badung Regency Government Office Centre are coming to or going home from their offices has created long lines of traffic jammed cars along Sempidi Road and the Dalung-Sempidi Road. Therefore, an analysis on the performance of the road and intersections around the Badung Regency Government Office Centre is needed to be done. The aim of this study is to identify the values of Trip Generation by Badung Regency Government Office Centre, the performance of Jalan Raya Sempidi, Jalan Raya Sempidi-Dalung, and the Hanoman Intersection. The method used was based on the Indonesian Road Capacity Manual (MKJI), 1997. The result of the analysis showed that the impact of Trip Generation by Badung Regency Government Office Centre during peak hours is 1,414 pcu/hour. Degree of Saturation on Sempidi Road increased from 0.93 to 0.97, and the Level of Service in E. Degree of Saturation on Sempidi-Dalung Road increased from 0.67 to 0.93 and the Level of service decreased from C to E. Degree of Saturation on Hanoman Intersection increased from 1.59 to 1.83 and the Intersection Delay increased from 160-109 to 229-150, and Level of Service in F. The traffic congestion in Raya Sempidi and Raya Sempidi-Dalung road are caused by the delay in Hanoman Intersection, therefore the problem in Hanoman Intersection must be solved. With the availability of land in the Northern and Southern gate of Badung Regency Government Office Centre, the solution can be in the form of establishment a U-Turn.